2009
DOI: 10.1088/1751-8113/42/20/205101
|View full text |Cite
|
Sign up to set email alerts
|

Phase-space geometry and reaction dynamics near index 2 saddles

Abstract: We study the phase space geometry associated with index 2 saddles of a potential energy surface and its influence on reaction dynamics for n degree-of-freedom (DoF) Hamiltonian systems. In recent years similar studies have been carried out for index 1 saddles of potential energy surfaces, and the phase space geometry associated with classical transition state theory has been elucidated.In this case the existence of a normally hyperbolic invariant manifold (NHIM) of saddle stability type has been shown, where t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 88 publications
0
63
0
Order By: Relevance
“…35 There is even richer variety of phase space structures and invariant manifolds associated with index two saddles of the potential energy surface, and their implications for reaction dynamics have begun to be explored. 27,31,32 Fundamental theorems assure the existence of these phase space structures and invariant manifolds for a range of energy above that of the saddle. 34 However, the precise extent of this range, as well as the nature and consequences of any bifurcations of the phase space structures and invariant manifolds that might occur as energy is increased, is not known and is a topic of continuing research.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…35 There is even richer variety of phase space structures and invariant manifolds associated with index two saddles of the potential energy surface, and their implications for reaction dynamics have begun to be explored. 27,31,32 Fundamental theorems assure the existence of these phase space structures and invariant manifolds for a range of energy above that of the saddle. 34 However, the precise extent of this range, as well as the nature and consequences of any bifurcations of the phase space structures and invariant manifolds that might occur as energy is increased, is not known and is a topic of continuing research.…”
Section: Introductionmentioning
confidence: 94%
“…To show that the vector field is nowhere tangent to the sampled surface, except on the NHIM, we must evaluate the flux form 27 associated with the Hamiltonian vector field through the DS on tangent vectors to the DS. The Hamiltonian vector field is not tangent to the DS if the flux form is nowhere zero on the DS, except at the NHIM.…”
Section: Sampling Of a Dividing Surface Attached To A Nhim For A 2 Domentioning
confidence: 99%
See 1 more Smart Citation
“…The phase space for the non-ergodic dynamics of a multi-dimensional polyatomic molecule consists of an Arnold web of corridors of irregular/chaotic motion traversing interconnected regions of regular motion [26,28]. A molecular understanding of intrinsic non-RRKM dynamics desires the identification of the specific mode excitations which lead to irregular or regular atomic-level dynamics [31][32][33][34][35].…”
Section: P(t) = I F I K I Ementioning
confidence: 99%
“…To reveal the fundamental mechanism of the passage through a saddle with an index greater than 1, the phase-space structure was recently studied on the basis of normal form (NF) theory [68][69][70][71]. For example, the pioneering studies to extend the dynamical reaction theory into higher-index saddles were reported [68] for concerted reactions.…”
Section: Introductionmentioning
confidence: 99%